Experiencia del profesional de enfermería ante la muerte y el proceso de morir en unidades de cuidado intensivo - Valle-Figueroa, María del Carmen (Universidad de Sonora, 2019)
Objective: The objective of this research is to understand the experience of the nursing professional with regard to the death of a patient. Methodology: Qualitative, descriptive, and cross-sectional study. Seven nurses of the intensive care unit of a secondary care institution participated. To select the participants, a typological classification was constructed including age of the patient, duration of the relationship, experience regarding death processes, and age of the nurse. Data analysis was performed in an inductive-deductive way; the software Nvivo, version 7, was used. This research is in line with the Regulation of the General Health Act in the Area of Health Research. Results: The participants informed that the main coping strategies with regard to death and the dying process are emotional detachment, as well as seeking social support in religious and thanatology groups, and psychological help. Innate mechanisms are part of cultural capitals, while those acquired are usually taught at educational and health institutions. Conclusions: The dying process is determined by three types of important contextual stimuli: Age of the patient, nurse-patient relationship, and length of this relationship. Efficient coping processes were found in those nurses, who, within their professional preparation, thanatology courses were included. Main coping strategies found were: redefinition of death and emotional support through some type of religious belief.